Genetic variability for yield and its components in indian mustard (Brassica juncea L. Czern & Coss) - Neelam Shekhawat, G. C. Jadeja and Jogendra Singh (Electronic Journal of Plant Breeding, 2014)
Study of 60 genotypes of Indian mustard (Brassica juncea L. Czern & Coss) for 13 different characters revealed considerable variability for all the characters under study. The eight characters viz., days to 50% flowering, days to maturity, number of secondary branches per plant, length of main branch, number of siliqua per plant, number of seeds per siliqua, test weight and seed yield per plant showed high estimates of GCV as well as high heritability. The characters like number of secondary branches per plant, seed yield per plant and number of siliqua per plant, in that order, exhibited high heritability and high expected genetic advance. Hence selection will be effective for these traits.